kOMPOSISI IKAN HASIL TANGKAPAN JARING INSANG PADA BERBAGAI SHORTENING DI WADUK SERMO - Supardjo S. Djasmani; Djumanto Djumanto (Jurnal Perikanan Universitas Gadjah Mada, 2014)
The aim of this study was to determine ﬁ sh capture and composition using gill nets in various of shortening nets, as well as to obtained a suitable size of shortening nets which better productive and sustainable. The study was conducted by ﬁ shing using gill nets 4 sheets, using gill net with mesh size of 2-inch eye openings and various shortening nets, namely 40%, 50%, 60%, and 70%. The setting gill nets were done in the afternoon and hauling the following morning day. Gill net setting were done once a week in September-October 2013. All species of ﬁ sh gilled were collected, then measured the length and weight, as well as on the abdomen was dissected to determine sex. Data on the number and weight of the catch were analyzed descriptively, analyzed using a completely randomized design were subjected to determine the best catches statistically. The results showed that the number of individuals ﬁ sh and the mean weight of ﬁ sh captured in shortening 40%, 50%, 60% and 70% were not signiﬁ cantly different. The most number of ﬁ sh captured was in the nets with shortening of 60%, ie 392.69 (g/ trip), then on shortening of 40%, ie 333.3 g / trip, next on the shortening of 50% as much as 285.9 g/trip and the least in shortening 70% as much as 263.6 g trip. Based on the ﬁ sh species composition, the most dominant of ﬁ sh captured was red devil (52.5%), then tilapia mossambique (27.1%), black tilapia (17.5%), managuin (1.3%), marbel gobby (0.8%), the remaining was consisted of snake head and javain carp (0.8%). Based on sex proportion, the proportion of male ﬁ sh in tilapia mossambique was 63.8%, black tilapia was 53.7%, and red devil was 58.2%, while the remaining was balance between male and female.